Difficult justice : commentaries on Levinas and politics - Horowitz, Asher, 1950-; Horowitz, Gad, 1936- (University of Toronto Press, 2006)
French philosopher and Talmudic commentator Emmanuel Levinas (1906?1995) is best known for his two major, highly original works on ethics, Totality and Infinity (1961) and Otherwise Than Being or Beyond Essence (1974). Among his lesser known works is a short but remarkable essay published in 1934,?Refections on the Philosophy of Hitlerism,? in which he considers German conservatism and the Nazi movement, and reflects on Western philosophy?s capacity to insure itself against?elemental evil.? Difficult Justice uses this essay as an introduction to a collection of papers on Levinas?s ethical and political thought. In this volume editors Asher and Gad Horowitz bring together contributors from a variety of disciplines and backgrounds to explore how Levinas?s work relates to a broad range of contemporary philosophical and political questions. In particular, they examine Levinas?s challenge to liberalism?to find another kinship for man? absolutely opposed to oppression,? and his movement beyond liberalism to embrace?the claim of the Other.? This thought-provoking collection will not only be invaluable to Levinas scholars, it will also be of interest to those working in the areas of Jewish studies, women?s studies, and political theory. Contributors:Keith AndersonShannon BellRobert BernasconiMielle ChandlerTina ChanterMarinos DiamantidesRosalyn DiproseEnrique DusselOona EisenstadtRobert GibbsAsher HorowitzGad HorowitzZe?ev LevyJoseph RosenBrian SchroederVictoria Tahmasebi.